2019
DOI: 10.1001/jamainternmed.2018.7289
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Ultraprocessed Food Consumption and Risk of Mortality Among Middle-aged Adults in France

Abstract: IMPORTANCE Growing evidence indicates that higher intake of ultraprocessed foods is associated with higher incidence of noncommunicable diseases. However, to date, the association between ultraprocessed foods consumption and mortality risk has never been investigated. OBJECTIVE To assess the association between ultraprocessed foods consumption and all-cause mortality risk. DESIGN, SETTING, AND PARTICIPANTS This observational prospective cohort study selected adults, 45 years or older, from the French NutriNet-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
264
3
21

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 313 publications
(316 citation statements)
references
References 56 publications
10
264
3
21
Order By: Relevance
“…Our results are in line with those obtained in the NutriNet-Santé Study. 29 According to our results, the strength of the association is probably higher than that presented in the NutriNet-Santé Study. This is especially important because young generations are increasing their consumption of ultra-processed food, and its consequences will be seen in the future.…”
Section: Interpretation and Comparison With Other Studiessupporting
(Expert classified)
See 1 more Smart Citation
“…Our results are in line with those obtained in the NutriNet-Santé Study. 29 According to our results, the strength of the association is probably higher than that presented in the NutriNet-Santé Study. This is especially important because young generations are increasing their consumption of ultra-processed food, and its consequences will be seen in the future.…”
Section: Interpretation and Comparison With Other Studiessupporting
(Expert classified)
“…Very recently, a cohort study conducted in France (the NutiriNet.Santé Study) assessed the association between ultraprocessed food consumption and the risk of mortality among middle-aged adults (45 years old and older). 29 Participants were highly selected (mainly women, and more health conscious than the general population), 30 and all the information was based on electronic data. The authors found a positive relationship between ultra-processed food intake and the risk of mortality.…”
mentioning
confidence: 99%
“…In fact, evidence to support its risk is growing, now extending also to incident cancer (30) and overall mortality (31) . With regard to obesity, our findings confirm the role of ultra-processed foods in incident overweight and obesity found by Mendonça et al and by one small study of weight gain in pregnancy (32) , as well cross-sectional evidence originated in different countries and settings, which almost uniformly suggests risk (10,27,(33)(34)(35) .…”
Section: Discussionmentioning
confidence: 99%
“…[15,22]. In addition to the poor nutritional value (high in calories, saturated fat, refined CHO, and salt, low in fiber), there are also concerns regarding the industrial processes involved, due to the use of contaminants and food additives [23,24]. Recently, Schnabel et al summarized different plausible risk factors linking the overconsumption of ultra-processed foods with cancer, as follows: (1) the high temperature of food processing may lead to formation of contaminants; (2) acrylamide may have a carcinogenic and genotoxic effect;…”
Section: The Killer: Which Nutrient(s)?mentioning
confidence: 99%
“…(3) the overconsumption of processed meat could predispose people to a high risk of stomach and colorectal cancer; (4) additives like titanium dioxide may be associated with increased risk of intestinal inflammation and carcinogenesis; (5) emulsifiers and abuse of artificial sweeteners may alter the gut microbiota, causing predisposition to colorectal cancer; and (6) food packaging may facilitate contact with toxic chemicals like bisphenol A, which is supposed to have endocrine-disrupting properties [23]. In conclusion, the overconsumption of ultra-processed foods may increase neoplastic risk due to exposure to potentially carcinogenic chemicals.…”
Section: The Killer: Which Nutrient(s)?mentioning
confidence: 99%